European Integration as a Process of Emergence of the Postmodern Supranational State - Stępkowski, Aleksander (Federalism as the Future of the Diverse EU?, 2025)
The chapter propose to consider contemporary process of European integration as a stage of a longer socio-political process that was initiated with the cultural change that took place during the Enlightenment. This process is determined in its substance by the intellectual categories underpinning modern intellectual culture. Today they inspire transgressive postmodern development of the culture. The chapter describes the way in which, implementation of this modern intellectual agenda predetermines trajectory of political development resulting in contemporary European integration. At first it demonstrates the way in which the agenda was aimed at the reconstruction of premodern society and resulted in the emergence of the modern nation-state. However, the modern state by no means appeared to be the accomplishment of this process. Instead, it has been continuing and contemporary achieved its new transgressive stage resulting in creation of postmodern supranational political structures gradually dominating over the modern nation-states. The chapter identifies striking similarities between the process of the formation of modern nation states and the contemporary formation of the postmodern supra-national state. It analyses process of European integration demonstrating the quest towards providing EU with the autonomous democratic legitimacy. Subsequently, this would allow to marginalise member states and the principle of conferral granting EU in the future with the unconstrained power to legislate. Advancement of this tendency is demonstrated in the European Parliament’s proposal for the amendment of the EU Treaties as adopted in November 2023.The chapter propose to consider contemporary process of European integration as a stage of a longer socio-political process that was initiated with the cultural change that took place during the Enlightenment. This process is determined in its substance by the intellectual categories underpinning modern intellectual culture. Today they inspire transgressive postmodern development of the culture. The chapter describes the way in which, implementation of this modern intellectual agenda predetermines trajectory of political development resulting in contemporary European integration. At first it demonstrates the way in which the agenda was aimed at the reconstruction of premodern society and resulted in the emergence of the modern nation-state. However, the modern state by no means appeared to be the accomplishment of this process. Instead, it has been continuing and contemporary achieved its new transgressive stage resulting in creation of postmodern supranational political structures gradually dominating over the modern nation-states.The chapter identifies striking similarities between the process of the formation of modern nation states and the contemporary formation of the postmodern supra-national state. It analyses process of European integration demonstrating the quest towards providing EU with the autonomous democratic legitimacy. Subsequently, this would allow to marginalise member states and the principle of conferral granting EU in the future with the unconstrained power to legislate. Advancement of this tendency is demonstrated in the European Parliament’s proposal for the amendment of the EU Treaties as adopted in November 2023.Keywords: modernisation, European integration, intellectual determinants of political process, modern nation-state, postmodern supranational state, administrative courts, constitutional courts.